Cottonwood Leaf Beetle Chrysomela scripta Fabricius (Insecta: Coleoptera: Chrysomelidae: Chrysomela) - Amelio A. Chi; Russell F. Mizell (EDIS, 2012)
The cottonwood leaf beetle is one of the most economically important pests of managed cottonwood, aspen, and some poplar and willow species. Often it is a severe pest of urban ornamental trees. This leaf feeder has several generations each year, may cause extensive leaf loss, and can consequently reduce stem volume up to 70%. This 6-page fact sheet was written by Amelio A. Chi and Russell F. Mizell, III, and published by the UF Department of Entomology and Nematology, June 2012.